UPAYA REVITALISASI OBYEK WISATA CURUG PONGGANG MELALUI PEMASANGAN SUSURAN TANGGA SEPANJANG AKSES JALAN PENDAKIAN - Soewono, Arka Dwinanda; Darmawan, Marten; Turnip, Juan Karell Fitzgerald; Gunawan, Harjadi (LPPM Universitas Bina Bangsa, 2024)
Ponggang Village, located in Subang Regency, West Java, possesses a tourist attraction in the form of Ponggang Waterfall. However, the management of Ponggang Waterfall as a tourist attraction still needs more attention. One of the challenges is that access to Curug Ponggang goes through a fairly steep trail, which still needs to be equipped with a railing to separate the road from the ravine, so the level of safety still needs to be improved. Therefore, the purpose of the service activities carried out by the Community Service Program team from the Faculty of Engineering at the Atma Jaya Catholic University of Indonesia is to design and build suitable railings on the access trail from Ponggang village to Curuk Ponggang to improve safety, comfort and smooth activities for village residents and visitors. The stair railing will be made from PVC pipe, steel wire, and jute rope. The existence of the railing will increase the potential of Ponggang Waterfall as a tourist attraction, especially for domestic tourists.